Trend of Degree of Collaboration of journals related to Humanities and Social Sciences published by Sri Lankan Universities - Navaneethakrishnan, S.; Weerasooriya, W.A. (Faculty of Graduate Studies, University of Kelaniya, 2014)
This study especially focuses on the degree of collaboration journals related to Humanities and Social Sciences published by Sri Lankan Universities. Degree of collaboration (DC) is defined as the ratio of the number of collaborative research papers to the total number of research papers in the discipline during a certain period of time. DC can also be applied to the individual journals to identify multi disciplinary nature of research articles produced by a group of authors of that particular journal. Twenty refereed journals related to Humanities and Social Sciences published of Sri Lankan universities during the period from 1968 to 2011, were analyzed in this study.The main objective of this study is to identify DC of these journals and to rank them according to their DC. The research method of this study was Quantitative method particularly Bibliometric analytical method. The required data for the analysis of this study was collected from 1903 records of the research articles published in the above said journals. Findings of this study illustrate that ‘Open University of Sri Lanka Journal’ was in the first rank with DC 0.536 followed by Vidyodaya Journal of Humanities and Social Sciences (0.286), Sabaragamuwa University Journal(0.277), Vistas (0.233), Journal of Social Sciences, Sri Lanka (0.200), Modern Sri Lanka Studies (0.111), International Law Journal (0.095), University of Colombo Review (0.072), Journal of the Faculty of Humanities and Social Sciences (0.037), Vidyodaya Journal of Arts Science and Letters (0.036), The Sri Lanka Journal of South Asian Studies (0.034), Modern Ceylon Studies (0.33). Rest of the journals has degree of collaboration less than 0.025. It was also observed that DC was generally increased according to the origin and development of the journals. Ancient journals have law rate and the journals originated later have high rate of degree of collaboration. The reason for this variation is because of the fact that the growth of interdisciplinary nature of researches. (314 words)
Keywords: Bibliometrics; Sri Lanka; Humanities; Social sciences; Degree of collaboration